A percepção sobre a doença em mulheres com câncer do colo do útero, mulheres com lesões precursoras e mulheres saudáveis - Aretz, Magnória (Universidade do Vale do Rio dos Sinos, 2012)
This dissertation consists of two articles, the first one being a systematic review of the literature and the second an empirical study. In study 1, it sought to conduct a systematic review of international literature regarding the perception of the disease and the cancer itself. 11 articles were found. The results showed that the studies are diverse and the focus of research is comprehensive, listing the perception about the disease and the cancer in various situations, especially in terms of quality of life. In study 2, the objective was to evaluate and compare the perceptions about cervical cancer found in three groups of women: 1) women diagnosed with cervical cancer and undergoing treatment for the disease; 2) women with uterine early stage cancer lesions or with HPV infections; and 3) women not having the disease nor the early stage cancer lesions. 150 adult women participated in the study at clinical gynecology and oncology outpatient clinics in two hospitals in Porto Alegre (RS). as instruments, the Demographic and clinical data sheet, the Questionnaire of perception about the disease Revised Illness Perception Questionnaire (IPQ-R) and Revised Illness Perception Questionnaire for Healthy People (IPQ-RH) were used. The results showed differences in perception between the groups in the identity dimensions (F = p < 0.001 11.654,), cyclic duration of disease (F = 4.416, p < 0.05) and causes of disease (F = 15.941, p < 0.001), which shows that healthy women showed positive perceptions in relation to disease, different from women with cancer and lesions. Perceptions among the three groups resembled each other in the following dimensions: length of the disease (acute/chronic), as a result of illness, personal control and consistency of treatment, disease and emotional representations.
Keywords: Percepção sobre a doença; Representação sobre a doença; Câncer de colo do útero; HPV; Illness perception; Illness representation; Cervical cancer; ACCNPQ::Ciências Humanas::Psicologia